Effect of Immersion in Calcium Chloride Solution on the Characteristic of Coconut Chips during Storage - Rindengan Barlina; Linda Trivana; Engelbert Manaroinsong (International Coconut Community, 2019)
The quality of coconut chips can be increased, through efforts to improve processing by immersing the coconut meat in CaCl2 solution. The various concentrations of CaCl2 solution are 0.0%, 0.5%, 1.0%, 1.5%, and 2.0%. Furthermore, the effect of treatments was evaluated on the characteristic of coconut chips for 0 months, 2 months, 4 months, and 6 months of storage in plastic coated aluminum foil packaging. The results showed that coconut chips from DMT coconut meat with fruit 9 months old contain 2.36-2.49% moisture, 2.36-2.55% ash, 3.87-5.35% protein, 37.31-45.35% fat, 50.15-53.23% carbohydrate and 4.93-5.48% crude fiber. Immersion in CaCl2 solution and storage time increased the water content of coconut chips. The results of organoleptic testing showed that coconut chips still preferred by respondent up to 6 months of storage. The higher concentration of CaCl2 solution was used, resulting in smaller pressure (gram force) to break or destroy coconut chips, which can be interpreted that coconut chips have a crispness that is still good. Next, the color measurement uses Chromameter Konica Minolta CR-400, L (Lightness) value to 6 months ranged from 76.39-77.65, which indicated that the color of the product is still predominantly bright white.